PROGNOSTIC VALUE OF BRAIN NATRIURETIC PEPTIDE IN PATIENTS WITH ACUTE CORONARY SYNDROME - Tytarenko, N.V.; Kopytsya, M.P.; Rodionova, Yu.V.; Petenyova, L.L.; Oparin, O.L. (World of Medicine and Biology, 2018)
Despite the obvious progress made in the last decade in the study of pathogenesis, diagnosis and treatment of acute coronary syndrome, it is still the main cause of mortality and disability in the developed countries. In Western Europe and the United States over 900 thousands people die each year from acute coronary syndrome. From this amount, 30-40% of all patients with acute coronary syndrome consist from myocardial infarction with ST-segment elevation and 60-70% - with unstable angina and myocardial infarction without ST segment elevation on electrocardiogram. As it has been shown by the results of prospective observational studies, the patients with acute coronary syndrome represent a heterogeneous prognosis group: in some it may be favorable, while in others the mortality within one year may reach 39%. In this regard it is important to provide risk stratification in this category of patients.Generally accepted predictor of unfavorable prognosis is increase of biochemical markers’ level. Currently, has seen increased interest in the study of neurohormonal activation and the role of brain natriuretic peptide (BNP) in determining the prognosis in patients with ACS. BNP is the only neurohormone, that produces ventricular cardiomyocytes in response to the volume load and pressure and can serve as a diagnostic marker of heart failure, and according to some scientists’ opinion, as a marker of the ischemia prevalence, which leads to disruption of mobility and to the increase of the myocardial wall stress. In this connection, we can assume that the level of BNP can serve as diagnostic (for diagnosis of heart failure and presence of ischemia) marker and prognostic factors in patients with acute coronary syndrome.The aim of this study was to define the utility of the measurement N-terminal pro-brain natriuretic peptide (NT pro-BNP) and other clinical and biochemical markers to predict lethal outcome at 6 months in patients with acute coronary syndrome.The prognostic value of NT-proBNP, other biochemical and clinical markers and their sum in relation to the development of the fatal outcome six months after the acute coronary syndrome has been studied. A total of 57 patients with acute coronary syndrome, received in the first day of the disease, were examined, 42 men and 15 women with an average age of 62.5 ± 4.7 years. The level of NT-proBNP was determined in all patients at the first day by the ELISA (Victor-Best, Russia). A characteristic curve (ROC curve) was constructed to detect the relationship between the first day NT-proBNP level and the prognosis of the fatal outcome 6 months after the acute coronary syndrome. The sensitivity and specificity of the NT-proBNP in the prediction of the fatal outcome were determined. According to the ROC data, the value of NT-proBNP > 1270.3 pg / ml was obtained as the threshold. Sensitivity of 44.4% and specificity of 97.9% allows to predict the fatal outcome 6 months after the acute coronary syndrome. The sensitivity of NT-proBNP in our sampling was not sufficient to detect patients at high risk of death 6 months after acute coronary syndrome. The construction of a mathematical model taking into account the summation of signs the level of NT-proBNP, age, hemoglobin level at admission, and the heart rate, allows to predict the mortality in patients with acute coronary syndrome with a sensitivity of 78% and a specificity of 96%.
Keywords: acute coronary syndrome; brain natriuretic peptide; prognostic value; lethal outcome